HUBUNGAN TINGKAT PENGETAHUAN, SIKAP DAN DUKUNGAN KELUARGA DENGAN SADARI PADA WANITA USIA SUBUR - Dora Lita Panjaitan; Eka Bati Widyaningsih; Nirmala Harahap (Politeknik Karya Husada, 2024)
Breast self-examination is one of the cheapest screening methods for early detection of breast cancer that can be carried out by women personally and according to their own schedule. The results of a preliminary study conducted by the author on 10 women of childbearing age at Midwife Zuhriyah's Independent Practice Place were 7 respondents (70%) who had never carried out an Independent Breast Examination for reasons of not knowing and not understanding. The aim of this research is to determine the relationship between the level of knowledge, attitudes and family support with breast self-examination in women of childbearing age at the independent practice of Midwife Zuhriyah in 2024. The method used is quantitative descriptive research with a cross-sectional design, with incidental sampling technique, large sample size totaling 82 respondents using primary data and analyzed using chi square. These results show that there is a relationship between the level of knowledge (p-value = 0.000, OR 21.600, CI 95%), attitude (p-value = 0.030, OR 3.366, CI 95%) and family support (p-value = 0.000, OR 16.185, CI 95%) by breast self-examination. The conclusion of this research is that there is a relationship between the level of knowledge, attitudes and family support and breast self-examination in women of childbearing age at the Independent Practice of Midwife Zuhriyah. It is hoped that midwives will educate women of childbearing age about the benefits and how to do BSE appropriately and correctly so as to increase knowledge and also triggers a positive attitude so that the number of BSE practices increases. Keywords: BSE, level of Knowledge, Attitude, Family Support